1970
DOI: 10.1113/jphysiol.1970.sp009039
|View full text |Cite
|
Sign up to set email alerts
|

Blood levels of oxytocin and vasopressin during suckling in the rabbit and the problem of their independent release

Abstract: SUMMARY1. Oxytocin and vasopressin were assayed in samples of blood collected from conscious rabbits during suckling. The milk yields were determined from the weight gain of the litters.2. With normal milk yields (35-155 g), relatively high concentrations (31-375 ,uu./ml.) of oxytocin were present in the blood but vasopressin was detected in only one out of eight samples. It is concluded that the release of oxytocin by the milk-ejection reflex is essential for normal milk removal in the rabbit and that this ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…37,47). Because under natural conditions rabbits are often both pregnant and lactating (8,38,51), the sudden surge in blood-born OT accompanying nursing (6,12,21,26) could induce abortion or premature birth were it not timed to occur during the period of minimum uterine sensitivity to OT, that is, during the night (43). The present findings thus show a close correspondence between uterine sensitivity to OT and the previously reported diurnal partitioning of nursing and parturition in this species (Ref.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…37,47). Because under natural conditions rabbits are often both pregnant and lactating (8,38,51), the sudden surge in blood-born OT accompanying nursing (6,12,21,26) could induce abortion or premature birth were it not timed to occur during the period of minimum uterine sensitivity to OT, that is, during the night (43). The present findings thus show a close correspondence between uterine sensitivity to OT and the previously reported diurnal partitioning of nursing and parturition in this species (Ref.…”
Section: Discussionsupporting
confidence: 69%
“…41, 47) just once every 24 h for ϳ3 min (13,38,40,51,68), at which time the pups drink up to 25% of their body weight (38,40,51). This rapid milk transfer depends on the large and sudden release of OT into the mother's bloodstream in response to sucking by the young (6,12,21,26). Rabbits also have a marked postpartum estrus and, under natural conditions, are often both pregnant and lactating (8,38,51).…”
mentioning
confidence: 99%
“…Evidence from other species confirms the view that suckling is a highly selective stimulus for the release of oxytocin. In the rabbit, for example, Bisset et al (1970) found that oxytocin appeared in the circulation during suckling without vasopressin. During the milking of cows, Legros, Reynaert & Peeters (1974) found that neurophysin I (i.e.…”
Section: Background Activity Of So Units During Sucklingmentioning
confidence: 99%
“…Four of the phasically active units were correlated with the oxytocin release for milk ejection. Three of these units displayed a burst of activity superimposed on the terminal portion ofan active phase, some 10 2-14*7 see INTRODUCTION The neurosecretory cells of the paraventricular (PV) and supraoptic (SO) nuclei of the hypothalamus have axons projecting to the neurohypophysis and form the efferent pathway for the neuroendocrine reflexes involved in the release of oxytocin and vasopressin following stimuli such as suckling (Folley & Knaggs, 1966;Bisset, Clark & Haldar, 1970), expansion of the birth canal (Roberts & Share, 1968;Haldar, 1970), dehydration (Jones & Pickering, 1969) and haemorrhage (Ginsburg & Brown., 1956;Bisset, Clark & Errington, 1971). PV and SO units have been identified in many studies by antidromic activation from the neurohypophysis (Yagi, Azuma & Matsuda, 1966;Cross, Novin & Sundsten, 1969) and the characteristics of their antidromic activation have been extensively investigated by extracellular (Dreifuss & Kelly, 1972a, b;Negoro & Holland, 1972;Barker, Crayton & Nicoll, 1971) and intracellular recording (Koizumi & Yamashita, 1972).…”
mentioning
confidence: 99%
“…OT, the twin neuropeptide of AVP, governs milk ejection after its release from the axon terminals of hypothalamic magnocellular neurons into the blood stream (Bisset et al 1970). During lactation, OT gene expression and OT immunoreactivity are increased in the magnocellular neurons of both the PVN and supraoptic nucleus (Wigger & Neumann 2002).…”
Section: Introductionmentioning
confidence: 99%